Missa eclectic: mass settings of the world church - Taylor, Joshua (Kansas State University, 2013)
Matthew and Mark both conclude their Gospel accounts of the first Mass, the last supper, the same way: “while singing a hymn they went out to the Mount of Olives.” Since the beginning of the Christian tradition the Mass has been accompanied by religious song. The structure of the Roman Mass grew, changed, and took its present form over the course of many years from the Ordo romanus I of ad 700 to the modern rite. The movements of the Mass Ordinary were all present in the Roman Mass as early as the 8th century, while the sections of the Mass Proper took longer to develop. Though early settings of the Ordinary were sung to modal chants, the introduction of organum and polyphony in the 14th century gave rise to inventions in compositions that continue to influence music history. Numerous composers have composed Mass settings for liturgical use. Through their work, these composers shaped compositional techniques and paved the way for additional settings of the Mass. Many other composers’ works have outgrown their liturgical use. Composers have used every form from a cappella missa brevis’, large-scale cori spezatti compositions, to orchestral works rarely intended for liturgical use. Following the Second Vatican Council (1962-1965) the liturgy could be spoken and set musically in the vernacular creating a new collection of compositions in a variety of languages. Movements from five compositions are the subject of this paper. Each piece was selected to for its compositional techniques from its respective time period and region of the world. The composers represent England, Brazil, Germany, France, and the United States.
Keywords: Music; Choral; Mass; Haydn; Vaughan Williams; Music (0413)